2015
DOI: 10.1111/petr.12573
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of autologous hematopoietic stem cell transplantation in children and adolescents with relapsed or refractory Hodgkin's lymphoma

Abstract: This study evaluates the outcome of 66 pediatric patients with rrHL who underwent autoHSCT. Twenty-nine patients experienced early relapse, and 19 patients experienced late relapse. Of 18 newly diagnosed with HL, 13 were primary refractory disease and five had late responsive disease. At the time of transplantation, only 68% of the patients were chemosensitive. The majority of patients received BCNU + etoposide + ara-C + melphalan for conditioning (45/66), and peripheral blood (56/66) was used as a source of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
1
8
2
1
Order By: Relevance
“…High‐dose chemotherapy followed by autologous hematopoietic cell transplantation (auto‐HCT) remains the standard treatment for medically fit patients with relapsed or refractory aggressive lymphomas . Reported survival rates 3 to 5 years after auto‐HCT for classic Hodgkin lymphoma (cHL) and diffuse large B‐cell lymphoma (DLBCL) range from 40% to 70% . Treatment failure is most commonly due to relapse or progression of the underlying disease, which primarily occurs within the first 2 years after auto‐HCT .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High‐dose chemotherapy followed by autologous hematopoietic cell transplantation (auto‐HCT) remains the standard treatment for medically fit patients with relapsed or refractory aggressive lymphomas . Reported survival rates 3 to 5 years after auto‐HCT for classic Hodgkin lymphoma (cHL) and diffuse large B‐cell lymphoma (DLBCL) range from 40% to 70% . Treatment failure is most commonly due to relapse or progression of the underlying disease, which primarily occurs within the first 2 years after auto‐HCT .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Reported survival rates 3 to 5 years after auto-HCT for classic Hodgkin lymphoma (cHL) and diffuse large B-cell lymphoma (DLBCL) range from 40% to 70%. [2][3][4][5][6][7][8] Treatment failure is most commonly due to relapse or progression of the underlying disease, which primarily occurs within the first 2 years after auto-HCT. 1 For those patients who survive the initial post-auto-HCT period, long-term outcomes are not well described.…”
Section: Introductionmentioning
confidence: 99%
“…The primary cause of transplant failure in this study appears to be relapse with a median time to relapse of 23.85 months post‐AHSCT and a relapse rate of approximately 20%. Others described a cumulative incidence of relapse to be 40% with most of their patients experienced late relapse > 12 months post‐AHSCT …”
Section: Discussionmentioning
confidence: 99%
“…No prospective, randomized pediatric trials comparing the effectiveness of AHSCT with that of standard chemotherapy in relapsed children with HL have been conducted. 16 Many investigators reported marked improvement of EFS compared to non-transplanted patients and reflecting on a better OS. 20,22 We describe in this study the outcome and prognostic factors of 43 patients with refractory/relapsed HL who underwent HDCT followed by AHSCT at a single cancer center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation